PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN MODEL NUMBERED HEADS TOGETHER PADA SISWA KELAS III SD NEGERI KARANGAWEN 1 TAHUN 2021/2022 - Rini, Heni Sulistyo (CV Sintesia, 2025)
This study aims to improve mathematics learning outcomes through the Numbered Heads Together learning model. The implementation of this class action is carried out in two cycles. Each cycle has one meeting. The research subjects were teachers and third grade students of SD Negeri Karangawen 1, totaling 30 students. Sources of data in this study are students and teachers. The form of this research is Classroom Action Research (CAR). The research procedure includes four stages, namely: planning, action, observation, and reflection. The results showed an increase in student learning outcomes.After using learning in the form of learning Number head together, student learning outcomes increased from the first one Judging from the pre-cycle students who completed there were 12 children or 40%, students who had not completed there were 18 children or 60%, in the first cycle there were 15 students or 50% students who had not completed, 15 students or 50% had not completed, and in the second cycle there are 30 students who have completed or 100%, there are no students who have not completed or 0%. This proves that the application of the Numbered Heads Together learning model is able to improve mathematics learning outcomes in third grade students of SD Negeri Karangawen 1, Karangawen District, Demak Regency.